2023
DOI: 10.3390/app13042186
|View full text |Cite
|
Sign up to set email alerts
|

Presenting Job Instructions Using an Augmented Reality Device, a Printed Manual, and a Video Display for Assembly and Disassembly Tasks: What Are the Differences?

Abstract: Components assembly and disassembly are fundamental tasks in manufacturing and the product service industry. Job instructions are required for novice and inexperienced workers to perform such tasks. Conventionally, job instructions may be presented via printed manual and video display. Augmented reality (AR) device has been one of the recent alternatives in conveying such information. This research compared the presentation of job instruction via AR display, video display, and a printed manual in performing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…The results of the incorrect boxes picked indicated that the participants made significantly more mistakes in picking the orders when using a paper list than when wearing a HoloLens 2. This was consistent with the findings in Dorloh et al's study [48], where they found that reading a paper menu involved significantly more mistakes in assembling a computer than when reading job instructions presented via a set of AR glasses. Lin et al [16] also found that the Microsoft HoloLens performed significantly better than a paper in terms of accuracy in their OP tasks.…”
Section: Accuracy Of the Op Taskssupporting
confidence: 91%
“…The results of the incorrect boxes picked indicated that the participants made significantly more mistakes in picking the orders when using a paper list than when wearing a HoloLens 2. This was consistent with the findings in Dorloh et al's study [48], where they found that reading a paper menu involved significantly more mistakes in assembling a computer than when reading job instructions presented via a set of AR glasses. Lin et al [16] also found that the Microsoft HoloLens performed significantly better than a paper in terms of accuracy in their OP tasks.…”
Section: Accuracy Of the Op Taskssupporting
confidence: 91%
“…Thus, it is important to maintain a high level of immersion [39] and training is de-tuned from distracting errors by the trainee [40]. In an experiment comparing paper tutorials, video tutorials, augmented reality, and virtual reality under constrained conditions, it was found that augmented reality led to the most satisfactory task performance [41].…”
Section: Introductionmentioning
confidence: 99%
“…Both VR and AR devices have become popular both for entertainment purposes and in the industry [42][43][44][45][46]. The literature [47] has shown that AR is one of the techniques that may facilitate the performance of workers in adaptive automation assembly systems (A3Ss).…”
Section: Introductionmentioning
confidence: 99%